Penerapan Upah Minimum Kota Kupang (UMK) bagi Pelayan Toko Pakaian di Kota Kupang Menurut Surat Keputusan Gubernur Nusa Tenggara Timur Nomor: 439/KEP/HK/2024 Tentang Upah Minimum Kota Kupang Tahun 2025 - Angelynzqha Febe Lapudo’ohs; Orpa Juliana Nubatonis; Petornius Damat (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The implementation of the Municipal Minimum Wage (UMK) in Kupang City has not been fully realized, as many clothing store employees continue to receive wages below the legal standard. This study aims to examine the compliance of employers with UMK regulations and to identify factors contributing to non-compliance. The research employs an empirical legal approach with a descriptive qualitative method. Data were obtained through interviews with workers, business owners, and government officials, as well as through literature review and documentation. The findings reveal a significant gap between legal provisions and actual practice, where workers’ wages remain far below the stipulated UMK. This condition indicates weak enforcement of labor regulations and limited awareness among workers regarding their rights. Non-compliance is influenced by internal factors, such as wage policies based on job position and length of service, and external factors, including unstable business income, informal employment status, and low legal awareness. The study highlights the need for stronger government supervision, more consistent law enforcement, and improved dissemination of labor regulations to ensure fair wage practices and better protection of workers’ rights.